please clear

Asked by rajvarshneytushar | 24th Sep, 2020, 12:44: PM

Expert Answer:

(2x + 4)2 - (x - 5)2 = 26x
→ 4x2 + 16x + 16 - x2 + 10x - 25 = 26x
→ 3x2  + 16 - 25 = 
→ 3x2  = 9
begin mathsize 16px style rightwards double arrow straight x squared space equals space 3
rightwards double arrow straight x space space space equals space plus-or-minus square root of 3 end style

So, the positive value of x which satisfies the given equation is begin mathsize 16px style square root of 3 end style.

Answered by Yasmeen Khan | 24th Sep, 2020, 01:10: PM